AUTHENTIC MATERIALS AND WRITING SKILLS OF STUDENTS IN FILIPINO - Momo, Marianjoy; Altaya, Gracelyn (International Journal of Arts, Sciences and Education, 2025)
This study aimed to present the effectiveness of authentic materials in enhancing the writing skills of students in Filipino. These authentic materials were used as instructional tools to effectively develop and improve students' writing skills. To address the study's objectives, 15 students from two selected sections of the ninth grade at North Dadiangas High School participated in achieving meaningful results. The research design employed was experimental, specifically a pre-test and post-test design, wherein the performance of a control group, taught using traditional methods, was compared with that of an experimental group, taught using selected authentic materials. This comparison aimed to determine the more effective approach in enhancing students’ writing skills in Filipino. The study's results confirmed that students who were taught using authentic materials demonstrated greater knowledge and proficiency in writing in Filipino. Their level of learning was significantly higher than that of students taught through conventional methods. Based on these findings, the researcher strongly recommends that teachers who teach writing skills in Filipino incorporate authentic materials in their instruction to make students' learning experiences more meaningful and effective.